Perceptions and Experiences of Beginner Investors In Making Investment Decisions in The Digital Era: A Qualitative Study of Investment Application Users - Muhammad Faried Pratama; Rachmawati; Rince Tambunan (PT. Maju Malaqbi Makkarana, 2026)
The rapid development of digital financial technology has significantly transformed investment activities by providing easier access to financial markets through digital investment applications. This study aims to explore the perceptions and experiences of beginner investors in making investment decisions in the digital era. Using a qualitative research approach with a phenomenological perspective, data were collected through semi-structured interviews with beginner investors who actively use digital investment applications. The collected data were analyzed using thematic analysis to identify patterns and themes related to investors’ experiences and decision-making processes. The findings reveal that investment decision-making among beginner investors is influenced by several interconnected factors, including the accessibility and usability of digital investment platforms, the influence of social media and online communities, the development of financial literacy, and psychological experiences related to investment gains and losses. Digital investment applications play a crucial role in lowering barriers to market participation by providing user-friendly interfaces and accessible financial information. However, reliance on social media as a source of investment information may also expose investors to misinformation and speculative investment behavior. In addition, emotional responses such as confidence, fear, and uncertainty often influence investment decisions among beginner investors. Overall, the study highlights that investment decision-making in the digital era is a multidimensional process shaped by technological accessibility, social influence, financial knowledge, and psychological factors. These findings contribute to a deeper understanding of investor behavior in digital financial environments and emphasize the importance of financial education and responsible investment practices.